The Role of Family and Community on Reducing Violence against Children - Ani Mardiyati (Jurnal Penelitian Kesejahteraan Sosial, 2015)
Children have the rights to live safely, comfortably, and happily, but not all children enjoy their rights. The rows of children become the victims of violence show that the protection on children is still weak. Children are part of a family. Children under five (Balita) are the weakest members in a family, because they are not able to defense themselves when athreat comes. The second group is children at six until 12 (primary school age). They are able to interact with outer world, even they still have a little experience on defending themselves, but at least they can ask for help through screaming. The third group is children at 13 to 18, they are able to anticipate the danger threatening them. The research was to reveal the relevancy of protection on children against violence. The children in this research are those between 1 to 12 ages. The research subjects were parents having children at those ages. To know the natures of protection, it needed informants as members of social welfare program (PKK) at city, under district, village, and community levels having cluster function ongirls and children protection. The research is qualitative-descriptive, revealing how far the family and community roles on children protection against violence. The result shows the first cluster having significant role on children protection was their close family, then environment community, and PKK motivators overseeing children and girls. Violence cases on children mostly done by their close family.